Penelusuran Bug Program Simulasi Pencetakan Transkrip SIAKAD Unila dengan Metode Whitebox dan Solusi Menggunakan Variabel Memori - Sakethi, Dwi; Wamiliana, Wamiliana; Wardhana, Wisnu; Zahroh, Alifah (Jurnal Komputasi, 2015)
AbstractIn tracking of SIAKAD transcript, there was found a bug, that is the arrangement of the lesson position at the tenth till fifteenth semester located between first and second semester. Process tracking bug did in simulation program. In this research, carried out a development of the original program Siakad as simulation program that will be analyzed, to find out where is bug in the system. Development this program using PHP and MySQL database software. Tracking bug using whitebox testing method, it can be determined whether there is a bug in the procedural structure of the program or just on the operational function of the system itself. Bugs can be repaired by adding some changes on source code of the program. The changes are determination of new variables as memory variables and application of Bubble sort method on sorting proccess. The result shows bugs on the program is fixed. Keywords: Bubble sort, Bug, MySQL, PHP, Siakad, Whitebox